The Influence of Current Ratio (CR) and Net Profit Margin (NPM) on the Share Price of PT Ultrajaya Milk Industry & Trading Company Tbk - Mohamad Fazar Fadilah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
The aim of this study was to determine and assess the simultaneous or partial effects of the current profitability ratio on stock prices at PT Ultrajaya Milk Industry & Trading Company for the years 2007–2017. This study used both a descriptive and an explanatory survey as its research approach. The financial statements of PT Ultrajaya Milk Industry & Trading Company for the years 2007 to 2017 serve as the study's analytical unit. In this study, the temporal horizon is time series, and the type of investigation is causation. Based on the study's findings, it was determined that PT Ultrajaya Milk Industry & Trading Company's current ratio for the 2007–2017 period actually produced positive analysis results, that the company's profitability for the 2007–2017 period was generally good, and that its stock price for the 2007–2017 period was reasonable. Profitability For the years 2007 to 2017, the current ratio to the share price of PT Ultrajaya Milk Industry & Trading Company had a strong simultaneous or partial impact. However, far than impacting profitability, the dominant current ratio also has an impact on stock prices.